A performance-based characterisation of CFRP composite deterioration using active infrared thermography. (1st June 2020) - Sarker, Munawar; Hadigheh, S. Ali Ali; Dias-da-Costa, Daniel
Abstract: This study explores the effect of sulphuric acid (H2 SO4 ) on the physical and mechanical properties of carbon fibre-reinforced polymer (CFRP) and its constituent elements including epoxy resin and fibrous reinforcement. Specimens are exposed to decreasing pH levels through an accelerated aging regime and subsequently tested by mechanical and non-destructive methods. Active infrared thermography is applied to develop a quantitative framework for material degradation. The effect of acid exposure is subsequently assessed through a performance criterion based on thermal energy variation. Microscopic analyses through scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) reveal the material degradation and impact of acid at the fibre-epoxy interface. Tensile testing on FRP and epoxy resin coupons indicate up to 25% reduction in strength. An acid attack model is developed for the environmental reduction factor ( CE ) that is shown to compare well with experimental data. The performance-based environmental reduction factor presented expands our understanding of the FRP material response to aggressive environments and its effectiveness during the in-service life of structure.